Analysis of Primary Value Chains in Slovenian Forest and Wood Bioeconomy - Jože Kropivšek; Aleš Straže; Dominika Gornik-Bučar (Drvna Industrija, 2024)
Green value chains are becoming increasingly important due to the current European and global strategic orientation. Wood and wood-related value chains are one of them. There are many challenges to overcome in the Slovenian forest-wood bioeconomy in order to strengthen it and make it more efficient. One of the biggest challenges is the increasing share of deciduous trees in Slovenian forests. This raises the question of how to build or strengthen forest-wood value chains with hardwood of different qualities as a basic raw material. The most important thing for the entire forest-wood bioeconomy is to have effective and functioning primary value chains in order to have a strong basis for multiplying the impact and value in the entire forest-wood value chain. The aim of this study was to analyze the primary value chains in the Slovenian forest-wood bioeconomy, with a focus on the processing of hardwood. The main research question was whether the primary value chains are equivalent for the efficient functioning of the forest wood chain, whose main raw material is hardwood. Based on an in-depth qualitative multi-criteria decision-making analysis, we can conclude that all analyzed primary value chains are very important for creating the conditions for the maximum utilization of the potential of hardwood raw materials of different quality. From the point of view of providing basic and advanced materials for further value chains in the wood sector (and related industries), these are mainly the chains P1 Sawlogs, P2 Veneer logs and P3 Wood for pulp and composites, and for other industries also the most advanced materials from the chain P4 Other industrial wood, which still require a lot of investment in research and development to reach the level of their wider (industrial) implementation. In terms of ensuring circular economy and sustainability, connecting chains C6 Residues and C7 Reclaimed wood are particularly important.